Analysis of potential carbon tax calculation schemes for steam power plant company registered on the Indonesia stock exchange - Mujiyati, Mujiyati; Putriani, Santi; Ulum, Halwa Qubailah Shobah; Ulynnuha, Ovi Itsnaini; A'zizah, Laila Oshiana Fitria (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This research aims to select the best scheme—carbon tax or carbon credits—based on Cap and Tax and Cap and Trade for Steam Power Plant Company (SPPC) listed on the Indonesia Stock Exchange (IDX), following the carbon tax requirement under the Harmonization of Tax Regulations Law Number 7 of 2021.Design/Methodology/Approach: This study employs qualitative descriptive analysis to simulate carbon tax calculations based on the minimum rates outlined in Indonesian regulations or to assess the cost of purchasing carbon credits, with the goal of identifying the most efficient scheme in accordance with the carbon market regulations set by the Financial Services Authority (FSA).Research findings: The analysis results show that paying for carbon is the right choice for SPPC because the cash spent is lower than buying an Emission Reduction Certificate (ERC).Theoretical contribution/ Originality: This study compares carbon tax payments and Emission Reduction Certificate (ERC) purchases in Indonesia, reinforcing legitimacy theory on taxpayer compliance and informing government tax policy. It also encourages public support for the Nationally Determined Contribution (NDC) policy.Practitioner/Policy implication: This study provides input for organizations in policy-making related to emission reduction obligations and supports the government's Economic Value of Carbon (EVC) policy, aiding infrastructure development and the goal of Net Zero Emissions.Research limitation/Implication: The data obtained was only 3 companies that had complete emissions reports from 2020 to 2022, but even though only 3 companies were able to reflect the choice of whether to pay carbon tax or buy ERC.